Cystic Fibrosis and Reproductive Outcomes: The Latest Insights into Fertility and Pregnancy - Weronika Małagocka; Karol Zagórski; Mateusz Kozik; Nina Skalska-Dziobek; Karolina Chybowska; Maria Naruszewicz; Przemysław Cetnarowski (Quality in Sport)
Introduction and purpose: Due to improvement in treatment of people with cystic fibrosis (CF), the number of adult patients increases. CF patients are living longer, with better quality of life and a growing number of them are considering parenthood. Most people with CF are suffering because of reduced fertility, however the number of pregnant CF patients rises. The aim of this paper was to summarize the date available in the literature and recent reports about the fertility, pregnancy and treatment of pregnant CF patients.